Do synergies pop up magically in digital transformation-based retail M&A: Valuing synergies with real options application - Andrejs Čirjevskis (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
This paper aims to explore and to illustrate success factors of reciprocal synergies of digital transformation-based merger and acquisition (M&A) deals in the grocery retail industry. The author carried out a case study on the merger of Ahold Delhaize in 2016. The paper's contribution is a conceptual model of research that helps in pre-acquisition analysis on competence-based synergies in M&A to value strategic synergies as market value added a using real options application. By combining qualitative and quantitative research methods, the author provides empirical evidence to indicate the validity and value of the proposed research framework for both scholars and practitioners alike.
Keywords: 650; digital transformation; merger and acquisition; real option; synergy